Impact Of Terrorism On International Trade In Pakistan - Equatora, Muhammad Ali; Raja, Ganes a/I; Anwar, Umar; Saeed, Hamid; Hussain, Syed Muzaffar (Politeknik Ilmu Pemasyarakatan, 2023)
International trade means buying and selling of goods and services. Foreign investments boost up economy and it brings lots of opportunities to develop such economy and thus such opportunity develops an economy. The development of such policies brings more investments and trade related opportunities within and outside the boundaries of the countries. This is only possible if the economy is stable because an investor always wants his investments to be safe and secure. Terrorism is a threat that is harming international trade. Due to terrorism trade in Pakistan had suffered a lot and the business opportunities are decreasing our industrialist are shifting towards other countries. Previous researches have concluded that terrorism is a threat that is affecting adversely the global markets and economy as well. The purpose of this research is to find out the impact terrorism is causing to the economy of Pakistan. The paper has also provided recommendations to cope with such threat. The results are extracted by using Microsoft Excel. Regression analysis has been used to identify the relationship between international trade and cost incurred on Terrorism. The results extracted had identified that cost incurred on terrorism have significant impact on international trade. To cope with the problem of terrorism and enhance international trade recommendations will be stated at the end.